Pengaruh Variasi Waktu Pemeraman Terhadap Nilai Uji Kuat Tekan Bebas pada Tanah Lempung dan Lanau yang Distabilisasi Menggunakan Kapur pada Kondisi Optimum - Hafizh Arrofiq, Abdil; Afriani, Lusmeilia; Iswan, Iswan (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
In this study used raw material such as silt and clay soil with a mixture of lime additive which has a variety of levels of 5%, 10%, and 15% as well as with a variety of curing time for 7 days, 14 days and 28 days.The purpose of this study to increase the compressive strength of silt and clay soil free them. Soil samples tested in this study represents silt soil from the village Yosomulyo, East Metro District, Metro City, while the clay is derived from Rawa Sragi, Jabung District, East Lampung regency.After doing research, from the third level, the compressive strength maximum free of silt and clay soil found in the levels of 15% with 28 days curing time. This is due to the greater levels of lime and the longer the curing time, the greater the unconfined compression value.Keywords: Clay Soil, Silt Soil, Unconfined Compression, lime.